2002
DOI: 10.21273/hortsci.37.1.208
|View full text |Cite
|
Sign up to set email alerts
|

Bermudagrass Establishment on High Sand-content Soils Using Various N-P-K Ratios

Abstract: For drainage, turfgrass is often established on sand-based soils, which are typically nutrient-deficient and require supplemental fertilization. The objective of this study was to determine the optimum N-P-K fertilizer ratio for establishing bermudagrass from sprigs in sand. `FloraDwarf' and `Tifdwarf' bermudagrasses [Cynodon dactylon (L.) Pers. × C. transvaalensis Burt-Davy] were sprigged on a United States Golf Association (USGA) green [85 sand: 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
31
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 1 publication
7
31
1
Order By: Relevance
“…In some treatments, applying P in excess of a 1.0-0.4 N-P ratio decreased coverage rate. The N part of the ratio remained constant across all treatments, with only P and K rates changing (Rodriguez et al, 2002).…”
mentioning
confidence: 94%
See 2 more Smart Citations
“…In some treatments, applying P in excess of a 1.0-0.4 N-P ratio decreased coverage rate. The N part of the ratio remained constant across all treatments, with only P and K rates changing (Rodriguez et al, 2002).…”
mentioning
confidence: 94%
“…When turf establishment on a putting green was studied, typical treatments included variations in the root‐zone mix (Murphy et al, 2005, 2001; Bigelow et al, 2001), P and K rates (Rodriguez et al, 2002), and mycorrhizal inoculation (Podeszfinski et al, 2002). One study used ultradwarf cultivars (Floradwarf and TifEagle, Rodriguez et al, 2002); the others evaluated creeping bentgrass. In the ultradwarf bermudagrass study, highest cover rates were reached when plots were fertilized at a 1.0–0.4–0.8 N–P–K ratio, with the N rate based on a weekly N application of 49 kg ha −1 In some treatments, applying P in excess of a 1.0–0.4 N–P ratio decreased coverage rate.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Rodriguez et al (2001) tested different fertilizer ratios on a sandy soil and found 100% of ground cover during bermudagrass establishment over a range of 5 to 11 wk after planting. Ground cover for the High rate was similar for both depths across the sampling period and reached 80% at about 85 and 101 DAP in 2012 and 2013, respectively.…”
Section: Frequencymentioning
confidence: 99%
“…Establishment and maintaining aesthetics and functional values of bermudagrass greens and tees includes identifying ideal application rates and seasonal applications of fertilizers, topdressing, and frequency of horizontal and vertical mowing and aerification (Bunnell et. al., 2005; Hollingsworth et al, 2005; Guertal and Evans, 2006; Rodriguez et al, 2001; White et al, 2004). After evaluation of vertical mowing and topdressing, management strategies for establishing and established ‘Tifdwarf’, Champion, FloraDwarf, ‘Miniverde’, and TifEagle ultradwarf bermudagrass cultivars in temperate Texas (White et al, 2004) suggested that cultural management will need to change as the cultivars mature.…”
mentioning
confidence: 99%